144k views
0 votes
Can someone pls show how to do this is with explanation

Can someone pls show how to do this is with explanation-example-1
User Thegauraw
by
5.4k points

1 Answer

5 votes

Answer:

The answer is true

Explanation:

1. Substitute -6 where you see M.

We do this is because M is equal to -6. So where we see another M, we automatically know that it is -6.

2. Rewrite the equation.

It should go from (-3m+2=20) to {-3 (-6)+2=20}

3. Solve it

-3 times -6 equals positive 18. In multiplication, a negative times a negative equals a positive. Then add the 2 and you get 20. So our answer is true.

Here's a visual walk through.

-3m+2= 20 m=-6

-3(-6)+2=20

-3(-6)= 18

18+2=20

User Edmund Lee
by
6.3k points